Status of Pesticide Residue in Grapes of Bijapur (Karnataka) - M.S. Yadawe, U.S. Pujeri, A.S. Pujar, S.C. Hiremath* (Recent Research in Science and Technology, 2010)
Abstract Grapes grown in Bijapur district (Karnataka) were analysed for pesticide residue content employing multiresidue analysis by gas liquid chromatography equipped with ECD and NPD detectors. All the fruit samples showed the presence of one or the other group of pesticides. Out of 8 samples analyzed only two samples showed pesticide residue content below the European MRL.Â The detected pesticides are Chlorothalonil, Chloropyriphos, Monocrotophos, Triazophos, Cypermethrin, Lamda Cyhalothrin, Matalaxyl, Flusilazole, Hexaconazole, Myclobutanil, Penconazole, Propiconazole, Triadimenol, Difenoconazole,Â Carbendazim,Â Azoxystrobin. On the bases of these studies it is suggested that pesticide residue monitoring should be extended to the grape grown for the supply in domestic market similar to the export quality, which may serve as basis for the future policy in chemical use. Keywords: Grape, Gas Liquid chromatography (GLC), Maximum Residue Limit (MRL), Pesticides